THE IMPACT OF VILLAGE FUND IMPLEMENTATION ON THE FARMERS’ EMPOWERMENT IN KONAWEHA VILLAGE, SAMATURU DISTRICT, KOLAKA REGENCY - Susiana Susiana; Rosmawaty Rosmawaty; Iskandar Iskandar (Jurnal Ilmiah Penyuluhan dan Pengembangan Masyarakat, 2022)
This studend aim to determined the impact of implementing village funds on farmer empowerment in Konaweha Village, Samaturu District, Kolaka Regency. This research was conducted from May to June 2022 with a total of 76 farmers as respondents. The sampling technique used is simple random sampling, and the data analysis used is descriptive statistics and simple linear regression. The data collection process was carried out by means of surveys and questionnaires, interviews, literature studies, and documentation. The results showed that the use of the Village Fund was high, meaning that the role of the village government had implemented indicators from the Implementation of the Village Fund, namely Communication, Resources, Disposition and Bureaucratic Structure well. The farmer empowerment program from the implementation of village funds is high, meaning that the empowerment of farmers in Konaweha Village, Samaturu District, Kolaka Regency is related to good Village Fund management, where the role of the village government is needed to achieve farmer welfare, farmer access, farmer critical awareness, farmer participation and farmer control.